Uma análise do uso de fóruns e comunidades virtuais colaborativas em uma instituição científica e tecnológica - Vieira, Gil Eduardo Amorim (2009)
The use of virtual communities and forums as tools making available tacit knowledge of employees, with a view to knowledge management in enterprises, has been used by many organizations. However, real results observed after implantation of these communities and forums have not matched expectations, mainly because they are seen high dropout rates. This paper describes and analyzes the experience of a government institution for science and technology in the adoption forums and virtual communities, through a case study, highlighting the critical factors for the implementation of such initiatives, as well as the main barriers encountered. Concludes that, despite efforts by the research institution, the results were influenced by the technological options adopted and the lack of complexity of the social processes involved. At the end of the work are presented best practices for implementing forums and virtual communities